The Implementation of Legal Certainty Principles in the Reporting Process of Debtor Bankruptcy Settlement by Curator to Supervisory Judge in Bankruptcy Practice - Holyness Singadimeja; Rai Mantili; Ema Rahmawati (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
After a debtor is declared bankrupt by Commercial Court, the debtor loses the rights to control and to manage assets. Debtor’s assets is under the management of curator, under surveillance of supervisory judge. Curator has important role in bankruptcy process since curator shall manage and maintain entire bankruptcy assets. Curator is expected to maximize value of bankruptcy assets to fulfill all debt obligations. Article 74 of the Law Number 37 of 2004 on Bankruptcy and Suspension of Payment, stipulates that curator must submit report to supervisory judge regarding the condition of bankruptcy assets and perform it quarterly. The report is disclosed to the public. The Article 74 is provision for supervisory judge to oversee curator’s performance in debtor’s bankruptcy settlement. Bankruptcy report from curator to supervisory judge in the Commercial Court can provide legal certainty for parties. In good faith, curator carries out duties and authorities to enforce the law on bankruptcy dispute resolution in Indonesia. The process of reporting debtors’ bankruptcy assets, in practice, is not carried out properly since there are no specific standards regarding the report. Further, there are no sanctions for violating curator. Consequently, the regulation cannot perform legal certainty. It is necessary to standardize reports and sanctions for violations because the report an important aspects of bankruptcy process for parties. Furthermore, curator’s responsibility to submit a report to supervisory judge is correlated to the principle of certainty in order to guarantee legal certainty as a principle of debt settlement. In Indonesia, the 1945 Constitution serves as a general ground; and the Law of Bankruptcy and Suspension of Payment functions as specific legal ground. If curator does not perform their duties properly, then they shall be responsible personally.AbstrakSetelah debitor dinyatakan pailit oleh Putusan Pengadilan Niaga, maka debitor kehilangan haknya untuk menguasai dan mengurus hartanya, sehingga segala pengurusan harta kekayaan debitor ada di bawah pengurusan kurator yang diawasi oleh Hakim Pengawas. Kurator memiliki peranan yang sangat besar dan sangat penting dalam suatu proses kepailitan karena kurator harus mengelola dan mengurus seluruh harta pailit sehingga nilai harta pailit tersebut dapat dimaksimalkan untuk memenuhi seluruh kewajiban debitor pailit terhadap hak para kreditornya. Berdasarkan ketentuan Pasal 74 UUKPKPU, disebutkan bahwa kurator harus menyampaikan laporan kepada hakim pengawas mengenai keadaan harta pailit dan pelaksanaan tugasnya setiap 3 (tiga bulan). Tujuan Pasal 74 UUKPKPU adalah agar hakim pengawas dapat mengetahui sampai mana kinerja kurator dalam hal melakukan pemberesan harta pailit debitor. Adanya laporan pemberesan harta (boedel) pailit oleh kurator kepada hakim pengawas di Pengadilan Niaga dapat memberikan kepastian hukum bagi para pihak, dengan itikad baik kurator menjalankan tugas dan kewenangannya guna penegakan hukum penyelesaian sengketa kepailitan di Indonesia. Proses laporan pemberesan harta pailit debitor dalam praktiknya tidak dilaksanakan dengan baik mengingat tidak ada standar khusus mengenai laporan yang dimaksud dan tidak adanya sanksi bagi kurator yang melanggar, sehingga pengaturan mengenai kewajiban tersebut tidak dapat mewujudkan kepastian hukum dalam praktiknya. Oleh karena itu, perlu diatur secara tegas mengenai standar laporan dan sanksi bagi pelanggarannya, mengingat pelaporan atas pemberesan harta pailit ini merupakan salah satu aspek terpenting dalam proses kepailitan baik bagi debitor maupun bagi kreditor. Lebih lanjut lagi, tanggung jawab kurator mengenai laporan pemberesan harta pailit debitor kepada hakim pengawas dihubungkan dengan prinsip kepastian agar dapat menjamin kepastian hukum sebagai sarana penyelesaian utang piutang di Indonesia adalah UUD 1945 sebagai landasan umum dan UUKPKPU sebagai landasan khusus. Apabila Kurator yang tidak menjalankan tugasnya dengan baik atau lalai, maka dapat bertanggung jawab secara pribadi.DOI: https://doi.org/10.22304/pjih.v5n3.a6